2014
DOI: 10.1002/path.4453
|View full text |Cite
|
Sign up to set email alerts
|

Prostacyclin‐synthase expression in head and neck carcinoma patients and its prognostic value in the response to radiotherapy

Abstract: Prostacyclin (PGI2 ) plays a role in cancer progression but the mechanism is currently poorly understood. Additionally, no data are available about the prognostic value of the PGI2 pathway in head and neck squamous cell carcinoma (HNSCC) therapy. We evaluated the expression of the PGI2 pathway in HNSCC patients. PGI2 production and PGI synthase (PGIS) expression, in terms of mRNA (RT-PCR) and protein (immunoblotting), were lower in tumour samples than in non-tumoural mucosa, whereas, as expected, COX-2 express… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
7
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
10

Relationship

1
9

Authors

Journals

citations
Cited by 13 publications
(7 citation statements)
references
References 39 publications
0
7
0
Order By: Relevance
“…A statistically significant correlation was also observed in head and neck squamous cell carcinoma. Patients who expressed high levels of PGIS in head and neck squamous cell carcinoma tissues had a higher 5-year survival rate than patients with low levels of PGIS 67 .…”
Section: Prostanoids and Cancermentioning
confidence: 89%
“…A statistically significant correlation was also observed in head and neck squamous cell carcinoma. Patients who expressed high levels of PGIS in head and neck squamous cell carcinoma tissues had a higher 5-year survival rate than patients with low levels of PGIS 67 .…”
Section: Prostanoids and Cancermentioning
confidence: 89%
“…Regarding the head and neck squamous-cell carcinoma type (HNSCC), a study has investigated carbaprostacyclin (cPGI 2 ), a stable analogue of PTGIS, and showed little effect of analogue in cell migration of the HNSCC cell line. Furthermore, the authors suggested that the effect of PTGIS was related to its ability to promote vascularization; also, PTGIS gene and protein expression were shown to be reduced in HNSCC samples compared to non-tumor mucosa [ 63 ].…”
Section: Discussionmentioning
confidence: 99%
“…Hypervascularization per se could be a determinant factor in reducing mechanical strength, because it turns the media layer spongy and favors leukocyte-mediated matrix degradation. We have shown that EP-4 activation, which is the main PGE-receptor in endothelial cells, induces angiogenesis [ 16 , 28 ]. Accordingly, MVEC-derived PGE 2 could play key role in the AAA-associated hypervascularization since PGE 2 could be more effective inducing angiogenesis in an autocrine manner.…”
Section: Discussionmentioning
confidence: 99%